ONE OF THE LIMITROPHE TERRITORIES OF THE GLOBAL WORLD (TRANSFORMATION OF THE STATES OF THE BALTIC-BLACK SEA REGION IN THE 21ST CENTURY) - ZAZHIGAEV, Boris (CENTRAL ASIA AND THE CAUCASUS, 2009)
In recent years the academic community has become increasingly engrossed in the conceptions of the Baltic-Black Sea system (BBSS)of international relations. Closer inspection reveals three major approaches. The first approach envisages the conceptual mapping of Europe (an idea suggested by Stein Rokkan)1 and its application in the Vienna-Moscow-Istanbul triangle. The second approach relies on the Cold War logic best described as conflicting interaction; it rests on the agency interpretation, which concentrates on military-strategic aspects and became especially obvious after the Russian-Georgian war of 2008. The third approach is best described as structural and interprets all changes as the geopolitical re-division of territories. The BBSS problem is undoubtedly topical. It was Halford Mackinder who pointed to the region’s geopolitical importance by tagging it as the World Island. It was pointed out long ago that the BBSS was formed by two continental rings, conventionally described as internal (formed by the East European and African-Arabian platforms) and external (formed, with a great degree of approximation, by the Hindustani, Chinese, and Siberian platforms). Europe, as part of the World Island, is fringed by the Mediterranean basin in the south and a pseudo-Mediterranean basin of the Baltics in the north. There is a fairly wide strip of intermediate territory of the Black Sea and the Baltic runoffs between Europe and the Heartland (formed by Eurasia proper). This makes the BBSS a link between Europe and Eurasia proper. Geographically we can identify a vast Baltic-Black Sea Mezhdumorie (inter-sea area) formed by two strips, one of them being part of the Baltic and the other of the Black Sea basins divided by the Carpathian Mountains that stretch meridionally between them. The river outflows of the Black Sea (the Dniester, Southern Bug, and Dnieper) are found to the east; they are adjacent to the rivers of the Baltic basin (the Nieman, Western Dvina, and the long rivers that flow across lakes: the Velikaia, Narva, Lovat, Volkhov, and Neva). This is a smaller inter-sea area of sorts, the pied-Carpathian bridgehead of Eurasia. The Danube basin, to the west of the Carpathians, latitudinally crosses the Small Carpathians (the Beskidy) to join the Vistula and Odra basins. From the geographical point of view, this much more complex and varied area falls apart into several interconnected territories and can be described as the Trans-Carpathian bridgehead of Europe. Political and economic activities in both geographical niches create mestorazvitia (development areas) associated, according to Samuel Huntington, for historical reasons with European and Eurasian civilizational confrontation and development. In other words, the geopolitical self-determination of these places was conditioned by the interaction of two civilizational entities—Europe proper and Russia-Eurasia. This geographic expanse can be described as mezhdumorie (an interface of two civilizations according to S. Huntington) with two civilizational orders—the pro-Western that tends toward Europe and the Eastern, which is mentally closer to Eurasia, Russia. On the whole, the BBSS can be described as a specific geopolitical entity at the junction of two vast geopolitical expanses—Western Europe and Russian Eurasia. It is wrong to think, however, that it tends either toward Europe or Eurasia. Throughout centuries this area acquired an intermediate civilization marked by a very specific mentality, culture, economic order, an undeveloped statehood, and the continuing efforts to find its place on the geopolitical map of Europe and the world.